Information & Communication Technology in Shaping Character During the Covid-19 Pandemic - Rachma Hasibuan; Nur Ika Sari Rakhmawati (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2021)
This study aims to describe how to foster childrens character throught the use of information technology when children learn at home. Seeing the current phenomena parents and PAUD teachers must be able to manage the existing situation. Shaping the character of the nation's children is very much needed through the habituation of the value of discipline in childhood that allows children to develop themselves into someone who has a noble character, praiseworthy and bring children to good behavior, especially in today's sophisticated technology. Children will get used to doing good for themselves and others by applying it at home. Disciplined personal habits are in the context of forming noble characters, namely whole people, who are skilled at speaking, using good symbols and cues, able to be creative and creative and appreciate the positive things in using information and communication technology that is increasingly advanced today.